PC Control Board : Type 3890 - Technical Description - Hps SystemTechnik
The PC control board - type 3890 is a universal interface for processing digital and analog signals in digital technology and in control engineering. For communication with IBM compatible PC the PC control board must be connected to the PC through the slot card (type 3890.1).